Development, implementation and evaluation of consultation case-based learning course to improve the interdisciplinary clinical reasoning ability-a pilot study from nephrology - Weiwei Kong; Ying Huang; Yingying Lu; Xiaoqi Shen; Chong Luo; Biyu Zhang; Yu Lin; Shaohua Chen; Xiayu Li; Fei Han; Jianghua Chen; Ying Xu (BMC Medical Education)
Abstract Background In modern clinical settings, interdisciplinary clinical reasoning skills and associated education are pivotal and should be encouraged for residency training. Methods An interdisciplinary course on clinical reasoning was developed for residents based on ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. We collected frequently encountered consultation cases as our teaching resources with the methods of scenario case-based learning. Finally, consultation case-based learning (CCBL) method was established. At the end of the course, summative evaluations were carried out to test the overall effects with the Kirkpatrick’s evaluation model. Results The ten-week interdisciplinary course were successfully implemented according to the planned training schedule. 26 residents from different majors were included, and 24 of the residents completed the modules and evaluation. Over 90% participants were satisfied with our course, and over 79.2% participants achieved improved interdisciplinary skills. Furthermore, 80% participants reported behavior changes in professional clinical practice after the completion of the course. Conclusions The interdisciplinary course based on consultation scenario case-based learning received positive feedback from most residents.